TRIPLE C reporting principles for case study evaluations of the role of context in complex interventions - Shaw, SE; Paparini, S; Murdoch, J; Green, J; Greenhalgh, T; Hanckel, B; James, HM; Petticrew, M; Wood, GW; Papoutsi, C (BioMed Central, 2023)
Background Guidance and reporting principles such as CONSORT (for randomised trials) and PRISMA (for systematic reviews) have greatly improved the reporting, discoverability, transparency and consistency of published research. We sought to develop similar guidance for case study evaluations undertaken to explore the influence of context on the processes and outcomes of complex interventions.